Transcription factor NF-κB in a basal metazoan, the sponge, has conserved and unique sequences, activities, and regulation. (March 2020) - Williams, Leah M.; Inge, Melissa M.; Mansfield, Katelyn M.; Rasmussen, Anna; Afghani, Jamie; Agrba, Mikhail; Albert, Colleen; Andersson, Cecilia; Babaei, Milad; Babaei, Mohammad; Bagdasaryants, Abigail; Bonilla, Arianna; et al.
Abstract: Herein, we characterize transcription factor NF-κB from the demosponge Amphimedon queenslandica (Aq). Aq–NF–κB is most similar to NF-κB p100/p105 among vertebrate proteins, with an N-terminal DNA-binding domain, a C-terminal Ankyrin (ANK) repeat domain, and a DNA binding-site profile akin to human NF-κB proteins. Like mammalian NF-κB p100, C-terminal truncation allows nuclear translocation of Aq–NF–κB and increases its transcriptional activation activity. Expression of IκB kinases (IKKs) induces proteasome-dependent C-terminal processing of Aq–NF–κB in human cells, and processing requires C-terminal serines in Aq–NF–κB. Unlike NF-κB p100, C-terminal sequences of Aq–NF–κB do not inhibit its DNA-binding activity. Tissue of a black encrusting demosponge contains NF-κB site DNA-binding activity, as well as nuclear and processed NF-κB. Treatment of sponge tissue with LPS increases both DNA-binding activity and processing of NF-κB. A. queenslandica transcriptomes contain homologs to upstream NF-κB pathway components. This is first functional characterization of NF-κB in sponge, the most basal multicellular animal. Highlights: Proteins in the immunity transcription factor NF-κB pathway are present in sponge. Activities and regulation of sponge NF-κB proteins are characterized. LPS treatment of sponge tissue activates NF-κB processing and DNA binding. NF-κB likely has a role in immunity in sponges, the most basal multicellular animals.